(3JGQjN eOjfI OeTbs - (3Ydj Hf GdMSf Hf gHI Gddg GdTGaYj GdOeTbj, CHh GdbGSe, KbI GdOjf, GHf YSGcQ , J (B571 (3g` s
(3ChdgG (B:s
(3CKfGA JQLeI HSQ Hf CHj CQWGI s
(3BNQgG (B:s
(3jfJgj HJQLeI KGHJ Hf CQbGe Hf KYdHI Hf YOj s
(3Vef eLehY , JQJjHgG (B: (3GdKGfjs
(3GdeLdO GdKGfj ef GdfSNI GdSGHbIs
(3hjMJhi Ydi GdCLRGA ef GdMGOi hGdJSYjf Edi GdJGSY hGdJSYjfs
(3hHBNQgG SeGYGJ HYVgG eDQN SfI (B573(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B273s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B331 ; (3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B566 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B84 s
Keywords: (3GdJGQjNs